Incidental Discovery of Testicular Microlithiasis: What Is the Importance of Ultrasound Surveillance Two Case Reports - F. Barchetti; V. De Marco; G. Barchetti; E. Pasqualitto; A. Sartori; M. Glorioso; S. Gigli; V. Megna; S. Montechiarello; V. Boncore; A. Stagnitti (Case Reports in Oncology, 2013)
Many studies have demonstrated an association between diffuse bilateral testicular microlithiasis (TM) and gonadal and extragonadal germ cell tumors. Nevertheless, it is still uncertain whether ultrasound surveillance is really necessary in patients with TM in the absence of other risk factors such as previous testicular cancer, a history of cryptorchidism or testicular atrophy. We report the cases of a 33- and a 39-year-old man presenting with a retroperitoneal extragonadal tumor. The first patient underwent an MRI examination in order to rule out a lumbosacral hernia: MRI images showed no slipped disks but a voluminous retroperitoneal solid mass. The histological analysis revealed an immature teratoma. The second patient came to the emergency department complaining of abdominal pain, vomiting, weight loss and mild jaundice: ultrasound examination showed a large, ill-defined heterogeneous abdominal mass, confirmed by CT and MRI examination. The histology diagnosed a yolk sac tumor. In both patients, the testicular sonography was performed to rule out a focal lesion, but it displayed bilateral TM without a focal testicular mass. Based on our direct experience, we highlight the importance of annual ultrasonographic surveillance of the testis and the retroperitoneal space in patients with occasionally detected TM.